Model of Exclusive Breastfeeding Social Support on Indonesian Working Mothers - Stang Stang; Fadlyah Muliah; Sumarni Marwang; Nurqalbi Sampara (Al-Sihah : The Public Health Science Journal, 2022)
Working mothers' status is one of the factors that have influenced exclusive breastfeeding. The availability of social support for working mothers can affect whether exclusive breastfeeding is successful. This study's objective was to examine the different types of social support and design a social support model for working mothers in Indonesia. This study employed mixed methods and an explanatory sequential design. There were 400 working mothers with babies ranging in age from 6 to 24 months. The study included 25 working mothers who provided exclusive breastfeeding (cases) and 25 individuals who did not provide exclusive breastfeeding (control). The sampling method was purposive sampling. There were 11 informants, including working mothers who breastfed exclusively, health workers, and healthcare cadres. This study found a significant relationship between social support from the husband (p=0.002), co-workers (p=0.010), parents (p=0.047), and workplace (p=0.002) and exclusive breastfeeding for working mothers. Only the social support of the husband and the workplace determine the social support model in exclusive breastfeeding for working mothers. A husband's contribution is essential in providing social support through emotional and instrumental support.